EuroBrake 2020 Technical Programme 2020
DOI: 10.46720/8442002eb2020-ebs-017
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization Method for a High Power Eddy Current Brake with a Magneto-isotropic Material Structure for the Use in Electrified Heavy Duty Trucks

Abstract: In electric vehicle applications, the braking technology has changed so that a part of the kinetic energy can be fed back into the battery with the traction machine. However in the case of an emergency brake the required braking power in a car is about 8 times and in commercial vehicle applications about 30 times higher than the drive power rating. This circumstance is the reason for the continued necessity of mechanical friction brakes. In large commercial vehicle applications, retarder technologies have a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…where M ec is the wear-free torque due to eddy currents, and M req is the total required torque (see Figure 1). In the first step, the active magnetic geometry is optimised exactly according to the method presented in [1], neglecting the additional frictional torque. At best, a hybrid brake with this geometry can achieve the wear reduction factor from optimisation in which the frictional torque is neglected.…”
Section: Design Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where M ec is the wear-free torque due to eddy currents, and M req is the total required torque (see Figure 1). In the first step, the active magnetic geometry is optimised exactly according to the method presented in [1], neglecting the additional frictional torque. At best, a hybrid brake with this geometry can achieve the wear reduction factor from optimisation in which the frictional torque is neglected.…”
Section: Design Methodsmentioning
confidence: 99%
“…In [1], it is shown that the disadvantage of a low power density can be compensated for by using a magnetoisotropic material structure. This structure allows the skin effect to be reduced and increases the free cooling area.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel zu der Lamellenbremse wurde im Projekt, beginnend mit der Auslegung über Modellbildung und Feldberechnung bis hin zu Konstruktion und Aufbau eine Induktionshybridbremse entwickelt, konstruiert, aufgebaut und validiert [10,11].…”
Section: Induktionshybridbremseunclassified